The Rietputs Formation in South Africa: A Pleistocene Fluvial Archive of Meteorite Impact Unique to the Kaapvaal Craton - Cavosie, Aaron; Erickson, T.; Montalvo, P.; Prado, D.; Cintron, N.; Gibbon, R. (John Wiley & Sons, 2018)
Reconstructing the terrestrial impact cratering record is a fundamental goal of planetary science. However, erosion, burial, and deformation can obscure or destroy impact records. A sedimentary record of impact is provided by detrital shocked minerals, which have been shown to survive erosion and transport in modern alluvium and Holocene glacial deposits. Here we describe detrital shocked minerals from a known impact structure in sediments that were transported to distal locations and buried. The Rietputs Formation is a Pleistocene fluvial terrace of the Vaal River in South Africa, and shocked minerals were found in the terrace at locations up to 750 km downstream of the 2020 Ma Vredefort impact structure. Optical and electron microscopy, and U-Pb geochronology, were used to establish microstructural and isotopic provenance indicators that demonstrate the detrital shocked minerals originated from the Vredefort impact structure. The Rietputs Formation contains fluvial diamonds and Acheulean (ca. 1.7–1.3 Ma) artifacts at sites such as Canteen Kopje, a South African National Monument. The assemblage of detritus in Rietputs Formation gravels, including shocked minerals from Earth’s largest impact structure, diamonds from Cretaceous kimberlites, and Stone Age artifacts, comprises a unique sedimentary archive of the Kaapvaal craton, and may have geoheritage significance.